Landscape design recommendation for passive recreational activities in Taman Rekreasi Indah - Lim, Julia Bee Phing (2014)
In this study, the existing site condition and the preference of users and resident nearby Taman Rekreasi Indah were identified in order to suggest a functional and aesthetic pleasing landscape design for passive recreational activities in Taman Rekreasi Indah. Preferences of users were identified through questionnaires survey. The survey was carried out involving 60 respondents and was selected randomly. The questionnaires consist of four sections which are demographic background, concern of landscape facilities and functionalities in general, contain information the on the perception of respondents toward the park and questions focusing on the respondents' preferences. Primary data collected from questionnaires and site inventory and analyses were used as foundation to design landscape recommendation master plan for passive recreation area of Taman Rekreasi lndah. From the questionnaires finding, many aspect in the park need to be improved as majority of the respondents have negative perceptions towards the park especially on the sense of security such as not visiting the park after sunset (mean value= 4.00), insecure seeing vandalism sign (mean value=4.13) and feel the park is safe had lowest mean value, 2.32. While site inventory and analyzes finding, the park not only lack in aesthetic value but also lack of facilities for passive recreational activities in the park. The important parts of the proposed landscape provide the users feeling of safe and enjoy the beautiful scenery while carried out recreation activities. CPTED was proposed in the Master Plan as it ensures the safety perceptions of users and improve life quality with proper design and use the physical environment effectively. Other negative elements that had previously prevented the people from visiting the park had been replaced with positive elements hoping that more people will visit the park.